Effect of bosentan on the production of proinflammatory cytokines in a rat model of emphysema - Kirkil, Gamze; Muz, Mehmet Hamdi; Deveci, Figen; Turgut, Teyfik; Ilhan, Fulya; Ozercan, Ibrahim (Nature Publishing Group, 2007)
Endothelin (ET) receptor antagonists have been developed to produce a reduction of ET related effects in various diseases, as well as in animal models of airway inflammation. We aimed to investigate the anti-inflammatory potential of bosentan on a rat model of emphysema. Thirty Wistar male rats were classified as control group (group 1), intratracheally (i.t.) instilled with saline, treated with vehicle solution; elastase group (group 2), i.t. instilled with porcine pancreatic elastase (PPE), treated with vehicle solution; and PPE+bosentan group (group 3), i.t. instilled with PPE, treated with bosentan. The levels of TNF-alpha, IL-1 beta, IL-6, and IL-8 in bronchoalveolar lavage fluid (BALE) and lung tissue, cell counts in BALF, and histologic analysis of all groups were evaluated. Neutrophile granulocytes (NG) and alveolar macrophages (AM) were increased more in group 2 than in group 1(P < 0.001, P = 0.04, respectively). Compared with group 2, neutrophil granulocyte (NG) and alveolar macrophages (AM) counts were decreased in group 3 (P < 0.001). Histological examination confirmed a diffuse neutrophilic inflammation and irregular alveolar air space enlargement in group 2. Treatment with bosentan partially reduced the enlarged lung volumes. Compared with group 1, the BALF levels of TNF-a and IL-6, and the lung tissue levels of IL-1 beta, IL-6, and IL-8 were increased in group 2 (P= 0.028, P= 0.005, P= 0.001, P= 0.019, P < 0.001, respectively). The TNF-alpha and IL-8 levels of BALF (P= 0.007, P= 0.001, respectively), and the TNF-a, IL-1(3, IL-6, and the IL-8 levels of lung tissue (P= 0.031, P= 0.017, P= 0.007, P < 0.001) were decreased in group 3 compared to group 2. In conclusion, bosentan decreased the inflammatory response by reducing numbers of inflammatory cells and pro-inflammatory cytokines.
Keywords: bosentan; endothelins; pulmonary emphysema; receptors; endothelin